The Effect of Jigsaw-Type Cooperative Learning Model with a Multimodal Approach on Students' Physics Concept Understanding - Lalu Azikri Amrullah; Gunawan Gunawan; Kosim Kosim (Indonesian Journal of STEM Education, 2026)
The low level of students' physics concept understanding is often caused by conventional learning processes and the lack of varied representational media. This study aims to investigate the effect of the Jigsaw-type cooperative learning model with a multimodal approach on students' physics concept understanding. This research employed a quasi-experimental method with a non-equivalent control group design. The population comprised all Grade 11 students at MA Nurul Iman, with samples selected via purposive sampling. Data were collected using a physics concept understanding test instrument consisting of multiple-choice items. Data analysis was performed using IBM SPSS Statistics 25, involving prerequisite tests followed by an Independent Sample T-test. The results indicated that the mean posttest score of the experimental class (84.29) was significantly higher than that of the control class (75.75). Hypothesis testing revealed a significance value (Sig. 2-tailed) of 0.018 < 0.05, leading to the rejection of H0 and the acceptance of Ha. Consequently, it can be concluded that the Jigsaw-type cooperative learning model with a multimodal approach has a significant effect on improving students' physics concept understanding. The integration of various representational modes effectively helps students visualize abstract concepts and strengthens cognitive construction through peer tutoring interactions.